The hydrogeology and restoration of a raised bog - Regan, Shane (Trinity College (Dublin, Ireland). Department of Civil, Structural and Environmental Engineering, 2013)
The occurrence of ecological communities of conservational value on the surface of raised bog wetlands requires that specific hydrological conditions are maintained. The management of raised bogs, as active peat-forming ecosystems, therefore requires an understanding of the relationships between regional hydrology and the hydroecological processes operating within the wetland system. Raised bogs are often considered to be isolated hydrological systems, separated from regional groundwater flows in underlying groundwater bodies. However, a wetland system does not need to be an outlet zone for groundwater discharge to be groundwater dependent. Research on Clara Bog, Ireland, indicates a more complicated relationship between the bog and regional groundwater system. This interconnection has significant implications for ecological engineering/ restoration design.
Keywords: Civil, Structural and Environmental Engineering, Ph.D.; Ph.D. Trinity College Dublin